CircITGA7 Suppresses Gastric Cancer Progression Through miR-1471/MTDH Axis - Jin, Haifeng; Wu, Zheng; Tan, Bibo; Liu, Zhen; Zhang, Binqian (Frontiers in Cell and Developmental Biology, 2021)
In recent years, there have been reports about the involvement of circular RNAs (circRNAs) in the pathogenesis of gastric cancer (GC), but the molecular mechanism in cell proliferation, invasion and migration is still unclear. Based on the TCGA database, we analyzed differentially expressed circRNAs between GC and non-tumor tissues. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis to clarify the functional role in GC. Here, we showed that circITGA7 was low expressed in GC tissues based on The Cancer Genome Atlas (TCGA) database. In vitro, silencing the expression of circITGA7 increased cell proliferation and metastasis, whereas overexpression did the opposite. Mechanistically, miR-1471 has circITGA7 as a sponge, and miR-1471 has MTDH as a target gene. Consequently, functional analysis showed that the tumor suppressor effect of circITGA7 was the result of regulating the miR-1471/MTDH axis. Overall, the circITGA7/miR-1471/MTDH signaling pathway may play a crucial role in GC, providing a new potential mechanism involved in GC progression.